Induction of paraptosis by targeting proteostasis exploiting the dysregulated translation of cancer - 이동민 (The Graduate School, Ajou University, 2022)
Most cellular processes are modified during tumorigenesis, leading to unlimited proliferation potential and resistance to apoptotic cues in cancer cells. Among these processes, the dysregulation of the protein synthesis is commonly observed, and it is believed to support the transformed phenotype of cancers. At the same time, paradoxically, cancer cells are well known to suffer from numerous stress conditions limiting protein translation and proliferation, including hypoxia, nutrient limitation, proteotoxic stress, and oncogenic stress. Thus, these backgrounds push cancer cells to adapt to diverse stresses and to depend on the maintenance of protein homeostasis, to support their continuous and unregulated proliferation. Here, I show that these cancerous characters come at a significant cost for cancer cells under proteotoxic stress conditions induced by inhibition of the degradation pathway. Under stress conditions, following eIF2α phosphorylation, integrated stress response (ISR) is activated, reducing canonical cap-dependent translation and inducing alternative translation pathways. I found that the inhibition of VCP, an essential protein for cellular proteostasis via promoting several protein degradation pathways, induces excessive proteotoxic stress and death selectively in cancer cells via oncogenic Akt-eIF3d-mediated translation rebound. I further found that the co-treatment of ISRIB, an ISR inhibitor, with bortezomib (Bz), a proteasome inhibitor (PI), enhanced the proteotoxic stress and paraptotic cell death in turn cancer cells. Overall, this study offers novel insights into how to kill cancer cells harboring oncogenic activation via a non-oncogene targeting regimen and the possibility of paraptosis as a potent anti-cancer strategy. Additionally, this data provide an understanding of the relationship between cancerous features and eIF3d-mediated translation as well as between less sensitive properties of the solid tumor to Bz and the role of ISR.
학위논문(박사)--아주대학교 일반대학원 :의생명과학과,2022. 2
Keywords: ISR; cancer; oncogene; proteostasis; translation